Pemanfaatan Limbah Fermentasi Biji Kakao (Theobroma cacao L.) Untuk Produksi Nata - Muhammad Alwi (Biocelebes, 2008)
Have been done a research which aim to know the pH and optimal sugar concentration at process of forming nata from cocoa seed dilution waste. Method used in this research experiment method by 16 treatment. Design was using a “Completely Randomized with composed of factorial” or Factorial RAL. The first factor is sugar concentration and secondary factor is acidity level (pH). The result of research indicate that formed by nata and thick and also different rendemen at all of given treatment. The treatment which is best is interaction sugar concentration 5% with pH 4 in thick forming nata that is 0,60 cm. and heavy rendemen nata of equal to 25,65%. Cocoa seed dilution waste result of fermentation can be made a alternative for the making of nata. Key words : Fermentation waste, Theobroma cacao, Nata